The Influence of the Work Environment and Work Discipline on Employee Performance in the Karawaci District, Tangerang City - Ahmad Rifa'i; Syamsuddin, Rahmi Andini; Rita Satria (International Journal of Educational and Life Sciences, 2024)
This research aims to determine the influence of the work environment and work discipline on employee performance in the Karawaci District, Tangerang City. The research method used in this research is descriptive quantitative. The sample method used was the Simple Random Sampling technique, with a total of 87 employees. The work environment variable (X1) obtained a coefficient of determination value of 9.7%. Hypothesis testing obtained calculated t value > ttable or (3.025 > 1.988) p This strengthened by a significance value of 0.03 <0.05. then Ho1 is rejected and H1 is accepted, meaning that the work environment has a partial influence on employee performance. The results of the work discipline variable (X2) obtained a coefficient of determination value of 54.5%. Hypothesis testing obtained t value > t table or (10.0091 > 1.988) p This strengthened by a significance value of 0.00 <0.05. With Thus , H02 is rejected and Ha2 is accepted It means that discipline Work own influence in a way Partial to performance employee . As for from variable environment work and discipline Work in a way simultaneous obtained mark coefficient determination of 57.2%, the simultaneous F hypothesis test was obtained The value obtained is fcount>ftable or (56.141 > 3.11), this is also reinforced by a significance value <0.05 or (0.00 <0.05). Thus, H03 is rejected and H03 is accepted, this shows that there is a significant simultaneous influence between the work environment and work discipline on employee performance in the environment. Subdistrict Karawaci, Tangerang City.